Potential Increase in Chili Crop Yield Through Superior Seed Selection Using an Intelligent System in Koya Barat, Papua - Prayitno, Joko; Firmansyah, Idris; Kahar, Gertrudis Vebriyanti (Jurnal Inotera, 2025)
This study discusses the development of a decision support system for selecting superior chili seeds using the Simple Additive Weighting (SAW) method. The main problem addressed is the difficulty in objectively determining the best seeds based on multiple criteria. An iterative development model was employed, allowing the system to be gradually improved. Black-box testing showed 100% compliance with the intended functionalities, while user testing using the User Acceptance Test (UAT) method achieved 85% in the “strongly agree” category, indicating that the system is easy to use and relevant to the problems faced by farmers in Koya Barat Subdistrict, Jayapura City, Papua. The analysis results recommend the Mellyana chili variety as the best seed choice. These findings demonstrate that this method effectively supports farmers’ decision-making in selecting superior chili seeds.